Resource management portal for laboratories using real devices on the Internet. - Zimmerli, Stefan
Internet-based distance learning is slowly gaining new territories and substituting current teaching methodologies. However, distance learning not only consists of transferring documents to web pages, but also of developing new concepts, methods, and implementation architectures. This article presents concepts and implementation issues for an example remote hands-on networking laboratory. The described course gives access to real network hardware via the Internet. In particular, authentication, authorization, scheduling, and error recovery issues had to be solved.
Keywords: Design; Experimentation; Human factors; Management; Measurement; Performance